The Context of State Level Policy Formation - Marshall, Catherine ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
Individual members of state legislatures wield the greatest influence in state level policy formation. This was one of the findings of a study that identified the power and influence context of state-level policymaking. Data were gathered from six states (Arizona, California, Pennsylvania, West Virginia, Wisconsin, Illinois) using an instrument devised to ask respondents their perceptions of policymakers' influence levels. While the six states provided an overall picture of power and influence, each state had its own individual picture. There were five levels of influence identified: (1) the Insiders made up of individual legislators and legislative bodies; (2) the Near Circle made up of professionals such as the Chief State School Officer and teachers' associations; (3) the Far Circle made up of interest groups and legislative staffs; (4) the Sometime Players made up of state school boards associations and administrative associations and; (5) the Often-Forgotten Players made up of courts, federal statutes, and non-education groups. Policy groups with high influence rankings were most likely to see their values incorporated into policy. A contributing factor to the wide variations among states is the differing perceptual screens of policymakers. Policymakers are socialized in distinctive cultures and share understandings about what is right in their state policy environment. This perceptual screen is termed the "assumptive worlds of policymakers." Any valid picture of educational policy should incorporate assumptive worlds. Tables analyzing the data state by state are included in the appendices. (SM)
Contract Number: NIE-G-83-0020.
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (San Francisco, CA, April 16-20, 1986).
Policymakers.
Researchers.
Administrators.
Practitioners.
Keywords: Administrators; Boards of Education; Decision Making; Educational Policy; Elementary Secondary Education; Legislators; Policy Formation; Politics of Education; State Government; State Legislation; State Officials; Superintendents; Teacher Associations; Arizona -- California -- Illinois -- Pennsylvania -- West Virginia -- Wisconsin; Speeches/Meeting Papers; Reports, Research